Faith is the place. The urban cultures of global prayers. - (:unkn) unknown (b_books, 2012)
Based on close cooperation between artistic and scientific researchers "Faith is the Place" explores how the new policies, economies, and cultures of faith in urban spaces are operating. also highlights the pictures and sounds, spaces, and practices created by the religious in the light of globalisation. The publication has emerged out of the traveling exhibition "the Urban Cultures of Global Prayers", creating knowledge and experiences of religious movements in space and generated with the means of artistic research. Within "Faith is the Place", the contributions presented in the exhibition by artists from eleven countries are complimented with further research results and alternate with essays on city and religion, art and science.
Keywords: Kultur; Stadtsoziologie; Stadtforschung; Großstadt; Kirche; Kultur; Entwicklungsland; Industrieland; Subkultur; Stadtkultur; Stadtgesellschaft; Religion; Alltag; Islam; Christentum; Glaubensgemeinschaft; Religionsgemeinschaft; Religiosität; Ethnologie